Smart rear-view mirror / Mohd. Razix Hamni Bahani, Muhammad Fareezs Diin Jamaluddin & Muhammad Fauzan Ayob - Bahani, Mohd. Razix Hamni; Jamaluddin, Muhammad Fareezs Diin; Ayob, Muhammad Fauzan (2015)
Driving during night absolutely risky and eyes dazzle will happen causes by the high light intensity that reflected at rear-view mirror. This high light intensity came from the vehicles at behind. From that, the main objective of this project is to overcome this problem. We design and develop the rear-view mirror and this project called Smart Rear-View Mirror. In the situation when there are light with high intensity came from behind vehicles, the smart rear-view mirror will block and reduce the light reflection at the mirror that will cause eyes dazzle. This is the main objective of this project. Some electronic component were design and develop into one product that help driver to overcome this problem easily. To produce the multipurpose product, we add some function into our project. This Smart Rear-View Mirror can help driver to get know the distance or range between own vehicle and vehicle at behind. A sensor place at behind vehicle and this sensor has ability to measure the range without physically touch or connection. While the measurement will display to driver as driver reading the cars speed meter. As result, driver can focus and become more comfortable while driving at the night. Eyes dazzle will no longer be the main problem that can disturb driver also can increase driver safely.